m-Health 2.0: New perspectives on mobile health, machine learning and big data analytics - Istepanian, Robert S.H.; Al-Anzi, Turki (Methods (San Diego, Calif.), 2018)
•m-Health 2.0 represents the evolution of mobile health in big data analytics and machine learning innovations era.•Smarter m-Health 2.0 applications will be developed as part of the ‘digital health’ evolution.•A new cognitive patient centric m-Health ecosystem will be increasingly used in different healthcare applications.•Many challenges remain in terms of privacy, security and ethical aspects.•‘Frugal m-Health systems’ will be important in targeting the healthcare demands of low-to-middle income countries. Mobile health (m-Health) has been repeatedly called the biggest technological breakthrough of our modern times. Similarly, the concept of big data in the context of healthcare is considered one of the transformative drivers for intelligent healthcare delivery systems. In recent years, big data has become increasingly synonymous with mobile health, however key challenges of ‘Big Data and mobile health’, remain largely untackled. This is becoming particularly important with the continued deluge of the structured and unstructured data sets generated on daily basis from the proliferation of mobile health applications within different healthcare systems and products globally. The aim of this paper is of twofold. First we present the relevant big data issues from the mobile health (m-Health) perspective. In particular we discuss these issues from the technological areas and building blocks (communications, sensors and computing) of mobile health and the newly defined (m-Health 2.0) concept. The second objective is to present the relevant rapprochement issues of big m-Health data analytics with m-Health. Further, we also present the current and future roles of machine and deep learning within the current smart phone centric m-health model. The critical balance between these two important areas will depend on how different stakeholder from patients, clinicians, healthcare providers, medical and m-health market businesses and regulators will perceive these developments. These new perspectives are essential for better understanding the fine balance between the new insights of how intelligent and connected the future mobile health systems will look like and the inherent risks and clinical complexities associated with the big data sets and analytical tools used in these systems. These topics will be subject for extensive work and investigations in the foreseeable future for the areas of data analytics, computational and artificial intelligence methods applied for mobile health.